(untitled) - Khemaissia, Sihem; Abaidia, Rachid; Houhoune, Fatima; Bennemla, Messaoud; Bayou, Naima; Haddad, Djamila; Benturki, Asma; Bendjeriou, Fatiha; Zermane, Faiza (Comptes Rendus. Chimie, 2025)
In this study, a porous adsorbent was synthesized hydrothermally from a molar composition gel of 10Na2O:Al2O3:100SiO2:2000H2O:20TPABr. X-ray diffraction confirmed the presence of a ZSM-12 zeolite phase, and nitrogen adsorption analysis revealed a Brunauer–Emmett–Teller specific surface area of 343.7 m2/g for the synthesized material. The ZSM-12 zeolite was then used for the recovery of uranium(VI) from aqueous solutions with initial uranium concentrations of 10 and 150 mg/L. Operating parameters such as pH, contact time, solid/liquid ratio, and temperature were systematically investigated. The optimum conditions were found to be consistent for both concentrations, with a pH value of 3, a contact time of 60 min, and a temperature of 20 °C. However, the solid/liquid ratio varied from 5 g/L for 10 mg/L uranium concentration to 8 g/L for 150 mg/L concentration. The Langmuir isotherm was well matched by ZSM-12, and its kinetics were consistent with the pseudo-second-order model. The adsorption of uranyl ions by ZSM-12 material is spontaneous, and both chemisorption and physisorption processes occur simultaneously during the adsorption. The thermodynamic parameters indicate that the adsorption of U(VI) on ZSM-12 is exothermic. The negative value of ΔS° indicates that the system disorder and randomness decrease as the adsorption proceeds and the liquid phase adsorbate components are immobilized on the surface of the adsorbent material.